Trends of Unnatural Deaths in Allahabad, Uttar Pradesh - Kaul, Archana; Rai, Rajesh Kumar; Srivastava, Prem Chandra; Agarwal, Priyanka; Rahat, Faraz; Sinha , U S (Journal of Indian Academy of Forensic Medicine, 2016)
Pattern of unnatural deaths is a reflection of the prevailing social set up and mental health status of the population. Periodic evaluation of trends of unnatural deaths may provide valuable data to adopt effective preventive measures in this respect. The aim of this study is to find out prevalent pattern of unnatural deaths in the local society throughout the year and how it is affected by age, sex, habitat, marital status and season. This study was conducted during March 2014 to March 2015 in Department of Forensic Medicine and Toxicology, Moti Lal Nehru Medical College, Allahabad. Out of 2958 post-mortem cases, 2690 (90.94%) were unnatural deaths. 1748 (64.98%) victims were male and remaining 942 (35.02%) were female. Married 2372 (88.18%) cases outnumber unmarried 318 (11.82%). Accidental deaths accounted for 1648 (61.26%) cases, suicidal deaths for 457 (16.98%) and alleged homicidal deaths for 275 (10.22%) cases. Maximum deaths 641(23.83%) were observed in age group 25-35 years in both sexes. Highest incidence was observed in rainy season and least (603) in autumn.